Assessing the Effectiveness of Visual Stimulation on Visual Perceptual Ability Among Intellectually Disabled Children - S. Seethalakshmi (International Journal of Evidence Based Nursing And Practices, 2023)
Every child, including those with mild mental retardation, has the right to receive an education. As like normal children, mild mentally intellectually disabled children need education that can help their growth and development and to perform their daily life activities. However, learning sources for intellectually disabled children have several obstacles, including recognition of objects. The purpose of this study is to orient the use of basic articles for mild intellectually disabled children that are used for day-to-day activities. The methodology used in this study employed a quantitative approach with a quasi-experimental design. Data collection techniques included observations and interviews conducted with mildly intellectually retarded children at Women's Voluntary Special School in Koundampalayam, Coimbatore. The data obtained from the study were analyzed using descriptive and inferential statistics. Based on the findings, it can be concluded that visual stimulation was successful in enhancing the visual perceptual ability of children with intellectual disabilities.
Keywords: Visual stimulation; intellectually retarded children; visual perceptual ability